2014
DOI: 10.18632/oncoscience.104
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of GPRC5A in diseases

Abstract: The ‘Retinoic Acid-Inducible G-protein-coupled receptors’ or RAIG are a group comprising the four orphan receptors GPRC5A, GPRC5B, GPRC5C and GPRC5D. As the name implies, their expression is induced by retinoic acid but beyond that very little is known about their function. In recent years, one member, GPRC5A, has been receiving increasing attention as it was shown to play important roles in human cancers. As a matter of fact, dysregulation of GPRC5A has been associated with several cancers including lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 90 publications
3
66
0
2
Order By: Relevance
“…GPRC5A is known to contain a binding site for CREB in the 5′ promotor region. Therefore, GPRC5A may form a negative feedback loop in which the phosphorylation of CREB is suppressed . The small molecule forskolin can promote CREB phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPRC5A is known to contain a binding site for CREB in the 5′ promotor region. Therefore, GPRC5A may form a negative feedback loop in which the phosphorylation of CREB is suppressed . The small molecule forskolin can promote CREB phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
“…GPRC5A participates in lung tissue homeostasis, and is expressed in pulmonary epithelial cells . Several reports showed that GPRC5A expression is increased in pancreatic cancer, colon cancer, breast cancer and myelodysplastic syndrome . On the other hand, GPRC5A has a dual behavior as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…GPRC5a is over expressed in pancreatic, breast, gastric and colon cancer, and it has been shown that overexpression of RAI3 predict poor prognosis in hepatocellular carcinoma [511]. Functional analysis of GPRC5a in different carcinomas indicated that RAI3 has pleiotropic effects and might confer resistance to Gemcitabine in pancreatic cancer, however the ligand of GPRC5a remains elusive [12], but GPRC5a overexpression might lead to a reduction of EGFR levels [13–16]. …”
Section: Introductionmentioning
confidence: 99%
“…GPRC5A also interacted with multiple proteins including EIF4A1 and HSPA9. Some studies even found GPRC5A was co-fractionated with GTF2F2, MPV17, NOLC1, SLC25A3, and EGFR in vivo [20,21]. GPRC5A was also involved in regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%